PENGARUH MOTIVASI, KETERAMPILAN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA UMKM KAIN TENUN IKAT HOUSE OF HOEDA’S DESA TROSO KABUPATEN JEPARA) - Ananingrum, Titi; Pradhanawati, Ari (Jurnal Ilmu Administrasi Bisnis, 2019)
This research is motivated by the achievement of employee performance targets that have not been determined by the UMKM Cloth Weaving House of Hoeda's Troso Village, Jepara Regency. The purpose of this study was to determine the effect of the variables Motivation, Skills and Compensation as variables x on Employee Performance as Y variables. The type of this study was explanatory research. With sampling technique saturated sampling to 34 people who are UMKM employees of Woven Fabric Ikat House of Hoeda's Troso Village Jepara Regency using the Saturated sampling method. This study uses simple regression analysis and multiple regression methods, using the t test as a hypothesis testing tool and the sobel test as a mediation test tool. This study uses SPSS version 20.0. The results showed that the Motivation variable had a positive influence on Employee Performance of 0.852. Skills have a positive influence on Employee Performance of 0.853. Compensation has a positive effect on Employee Performance of 0.615.